PEMBERDAYAAN KELOMPOK TANI MOIR MODUNG MELALUI KANDANG CLOSED HOUSE UNTUK MENINGKATKATKAN KAPASITAS BUDIDAYA TERNAK BABI DI DESA RIBANG, KABUPATEN SIKKA - Viktor Eko Transilvanus; Maria Yohanista; Maria Viviana Nurak Lewar; Elisabeth Pa'a; Ermelinda Owon (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
African Swine Fever (ASF) is a highly fatal viral disease in pigs caused by a double-stranded DNA virus of the genus Asfivirus (family Asfarviridae). The virus is environmentally resilient and can survive in blood, meat, and pig housing, often leading to mass mortality. Infection with virulent strains results in acute to peracute ASF, characterized by high fever, internal and external hemorrhages, and sudden death, with mortality rates exceeding 90% within three to ten days. The Modung Mior Farmers Group in Watuwelut Hamlet, Ribang Village, Koting District, Sikka Regency, consisting of ten members and raising six pigs in 2024, experienced sudden and simultaneous livestock deaths due to ASF. A limited understanding of Closed House (CH) systems and biosecurity practices reduced the group’s performance, lowering motivation to raise pigs during the 2019–March 2025 ASF outbreak and decreasing household income. The Primary Community Empowerment Program (PMP) aims to enhance the group’s competence and motivation through human resource management training and the construction of CH pig housing with strict biosecurity measures. The methods applied include socialization, training, technology implementation, and mentoring. The program outcomes show improved knowledge regarding ASF symptoms, transmission sources, prevention measures, barn-area zoning, biosecurity actions, and post-ASF reproductive management. The group now operates a CH-model pig pen equipped with para nets and insect nets (mesh 40) and applies routine disinfection. Additionally, members’ motivation to rebuild pig farming has increased, relationships within the group have become more supportive and open, and a business analysis comparing conditions during and after the ASF outbreak provides a foundation for developing the group’s entrepreneurship.